COMPREHENSIVE INVESTIGATION OF THROMBOPHILIA MARKERS IN THE PATHOGENESIS AND RECURRENCE OF VENOUS THROMBOEMBOLISM: A REVIEW (The Research of Medical Science Review, 2025)
Venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), is a significant cause of preventable morbidity and mortality worldwide. It arises primarily due to a combination of factors described by Virchow’s triad: venous stasis, endothelial injury, and hypercoagulability. VTE can affect individuals of all ages but is particularly common in hospitalized, surgical, and immobile patients. Several risk factors contribute to its development, including cancer, trauma, pregnancy, hormone therapy, genetic predisposition, and prolonged immobilization. Timely and accurate diagnosis is essential and typically involves a combination of clinical assessment, D-dimer testing, and imaging techniques such as Doppler ultrasound for DVT or CT pulmonary angiography for PE. Management focuses on anticoagulant therapy, with direct oral anticoagulants (DOACs) now widely preferred due to their safety and ease of use compared to traditional therapies like warfarin. Preventive strategies, including pharmacologic prophylaxis and mechanical methods, are crucial in high-risk populations. Despite advances in treatment and prevention, challenges such as bleeding complications and underdiagnosis persist. This report reviews the latest literature on the epidemiology, pathophysiology, diagnosis, treatment, and prevention of VTE, emphasizing the need for continued research and awareness to improve patient outcomes and reduce the global health burden of this condition.